The Relationship Between Social Support and Life Satisfaction Among Elderly Nursing Home Residents in Tehran - Mohammad Babapour; Ghoncheh Raheb; Mostafa Eglima (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: The purpose of this study was to investigate the relationship between social support and life satisfaction in nursing home residents in Tehran. Methods & Materials: The study was a cross-sectional-correlational research. The statistical society consists of all elderly people living in nursing homes in Tehran. The sample size which reduced to 150 (105 males and 45 females) of the 3, 10 and 20 urban districts of Tehran through cluster and random sampling methods. Measurement instruments were Vaux social support questionnaire (SS-A) and Diener life satisfaction questionnaire. Data were analyzed using SPSS-17 software through descriptive (mean and standard deviation) and inferential statistics (independent t test, Pearson correlation, Kolmogorov-Smirnof and enter sample liner regression). Results: The results showed that there was a significant relationship between social support and life satisfaction in elderly nursing home residents (P=0.035), However, significant differences was not found in social support (P=0.082) and life satisfaction (P=0.061) betweenelderly men and women. Regression analysis indicated that social support has a liner relationship with life satisfaction, and can predict its changes. Conclusion: Based on mentioned results, receiving social support from family, friends and acquaintances, can contribute to a greater life satisfaction in the elderly living in nursing homes.